Palynological Investigation of Some Astragalus L. Species Distributed in Şanlıurfa - Altın, Fatma; Akan, Hasan; Çeter, Talip (Igdir University, 2024)
In this study, pollen morphologies of 5 species (Astragalus guttatus Banks & Sol., A. cretaceus Boiss., A. caprinus L., A. brachystachys DC. and A. ancistrocarpus Boiss. & Hausskn.) belonging to the Astragalus genus of the family Fabaceae, which are distributed in Şanlıurfa province, were exemined by light and electron microscope. As a result of the study, it was determined that the pollen of the taxa were monad, radial symmetrical and isopolar. Pollen of all studied species are trizonocolporate, colpus length (Clg) 16.5-27.62 µm, colpus width (Clt) 2.15-4.16 µm, pore length (Plg) 6.69-9.32 µm, pore width (Plt) was detected between 6.69-11.44 µm. Polar axis length was measured between 19.23-33.66 µm and equatorial axis diameter was measured as 14.95-28.61 µm. Ornamentation was determined as psilate, psilate-perforate, psilate-microreticulate, microreticulate in the polar region and aperture surround the while microreticulate in the equatorial region. As a result of the study, it was determined that the characters such as pollen shape, pollen size and surface ornamentation differ between species and these characters have taxonmic value in the systematic separation of species.
Keywords: Astragalus; Palinoloji; Şanlıurfa; Bitki Bilimi (Diğer); Botany (Other); Astragalus; Palinology; Şanlıurfa; 15. Life on land